Analysis of Mathematical Representation Ability Development in Secondary High School - Rahayu, Wardani; Zakiah, Rizka (International Journal of Engineering and Technology, 2018)
This study aims to determine the development of mathematical representation skills of junior high school students (SMP) based on mathematical exam results data in 2014-2016. The research data was obtained from responses of students' answers consisting of 1,535 students in 2014 and 2,000 students in 2015 and 2016 classified based on indicators of mathematical representation ability. In addition, the classification of student response data is also by gender and type of school. This research is a descriptive research using tables and graphs to describe data analysis of the development of the ability of mathematical representation in each year. The results show that the average percentage of mathematical representation ability of junior high school students in creating and using representations to organize, record and communicate mathematical ideas decrease every year. In indicators uses representation to model and interpret the physical, social, and mathematical phenomena increase in 2014 to 2015 but decrease in 2016. In general, the average percentage of mathematical representation ability of male students is higher than female.Â Â Â